Pattern of newborn babies delivered by cesarean section - Guslihan D Tjipta; Riza I Nasution; Dachrul Aldy; Zakaria Siregar (Paediatrica Indonesiana, 2003)
Background The birth rate in Indonesia is still high and abnormallabor constitutes 15% of all deliveries which needs cesarean sec-tion as a solution for complicated cases.Objectives To find the general physical condition of babies bornafter cesarean section as well as the characteristics of motherswho underwent cesarean section.Methods A retrospective study on newborn babies delivered bycesarean section conducted in Subdivision of Neonatology, Medi-cal School, University of North Sumatera-Pirngadi Hospital Medan,in period of 2 years (1991-1992).Results There were 8762 babies born during the study period,1484 babies (16.93%) delivered by cesarean section due to pla-centa previa (26.2%), prolonged labor (15.8%), cephalopelvic dis-proportion (10.3%), neglected labor (9.9%), eclampsia/preeclamp-sia (8.1%), fetal distress (7.5%), previous section (6.6%), breechpresentation (5.7%), solutio placenta (4.0%), and others (5.9%). Itwas shown that mothers undergoing caesarean section was mainly20-30 years old (66.4%), multigravida (47.8%), term gestationalage (79.4%), and minimal antenatal care (61.3%). There were 1224(82.5%) babies with birth weight >2500 grams and 894 (60.2%)suffered from asphyxia.Conclusions The evidence of asphyxia by cesarean section andlow birth weight group was significantly different from those nor-mally delivered (p<0.001). The mortality rate was 11.5% due tostill birth 29.2%, RDS 18.3%, sepsis 15.5%, pneumonia 12.3%,and gastroenteritis 11.5%